Declining attendance at conferences locally and globally: How to combat in limited resource settings? (Journal of Psychiatrists' Association of Nepal, 2023)
Nepal is hosting several national and international conferences. This trend is growing in the past few years. It is heartening to see academicians and researchers from all over Nepal are taking up the responsibility with big enthusiasm for hosting such events. This gives hope to new and potential conference venues for the future. Such events especially in the field of psychiatry help create awareness and decrease stigma among colleagues of other specialty as well.